Comment on: Forearm oxygenation and blood flow kinetics during a sustained contraction in multiple ability groups of rock climbers. Issue 22 (16th November 2016) - Halsey, Tim; Callender, Nigel
ABSTRACT: We read with interest the authors' paper on this important area of climbing physiology. We however wish to highlight the incorrect identification of flexor carpi radialis (FCR) as a finger flexor and the implications it has for the conclusions described. FCR is a wrist flexor and has no direct bearing on flexion of the fingers during a climbing grip and thus could be expected to have a reduced oxygenation response compared to flexor digitorum profundus. We also would like to seek clarification from the authors regarding their confidence in their method for locating the two muscles under investigation as we feel this may not be accurately possible using the method described.